Specificity of Isoniazid on Growth Inhibition and Competition for an Oxidized Nicotinamide Adenine Dinucleotide Regulatory Site on the Electron Transport Pathway in Mycobacterium phlei - Davis, William B. (Antimicrob Agents Chemother, 1977)
The mechanism of action of isoniazid (INH) on saprophytic and atypical mycobacteria is thought to be different from that on Mycobacterium tuberculosis because higher concentrations are required to be effective in these species. In this investigation, M. phlei was inhibited by INH at a concentration of 25 μg/ml. Benzoic acid hydrazide (BZH) and nicotinic acid hydrazide (NAH) were inhibitory at levels of 300 and 500 μg/ml, respectively. Inhibition by these compounds was not inoculum dependent. An isolated M. phlei mutant resistant to 100 μg of INH per ml (Inh(r)) was inhibited by INH only at concentrations about equal to those inhibitory for BZH and NAH. When NAH and BZH were below their minimal inhibitory concentrations, INH inhibition was antagonized. Hence, there appears to be a single target site for INH in mycobacteria with different affinities for various hydrazide analogs of INH. The increased inhibitory levels required for the atypical and saprophytic species are due to a decreased affinity of the target site for INH in these species. INH also inhibited both the oxidized nicotinamide adenine dinucleotide (NAD(+)) and adenosine 5′-monophosphate stimulation of reduced NAD (NADH) oxidase activity associated with the M. phlei and M. tuberculosis H(37)R(a) electron transport particles. INH did not reverse the NAD(+) stimulation of oxidase activity in the Inh(r) strain of M. phlei. No direct inhibitory effect of INH on NADH oxidase activity was observed. Incubation of M. phlei electron transport particles at 0°C with INH resulted in a dramatic loss of oxidase activity which could have been prevented if NAD(+) were present. However, INH had no effect upon the NADH oxidase when stored with electron transport particles isolated from the Inh(r) strain. Therefore, INH inhibition of regulation and/or stabilization of the electron transport pathway by NAD(+) or adenosine 5′-monophosphate may account, in part, for the lethal action of the drug on mycobacteria.